Time-dependent quantum study of three-dimensional inelastic scattering of I-H2 - Gogtas, F; Bulut, N; Oturak, H; Kökce, A (Elsevier, 2002)
We have calculated the state-to-state inelastic scattering probabilities for three-dimensional inelastic scattering of I + H-2(v,j) --> I + H-2(v(t),j(j)) at zero total angular momentum. The state,to-state probabilities show broad oscillations with some large resonances imposed on them. The total reaction probability which is unity in the low energy region drops down in the high energy region where the H-2 molecule tends to dissociate. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: inelastic scattering; wave packet study; reaction probabilities